The Effect of Nursing Process Education on Students’ Perceptions of Nursing Diagnoses - Ezgi Bağrıaçık; Burcu Totur Dikmen (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
The aim of this study is to evaluate the effect of nursing process education on nursing students' perception of nursing diagnoses. This quasi-experimental study was conducted with the second-year students who took the course of internal medicine nursing. One hundred and eleven second-year students (91.72%) who were attending a nursing faculty were included in the pretest. Each of the training sessions given to the students lasted for 60 minutes, and a total of 12 sessions of training were applied as three sessions per week. The online training was given to students by an educator with a presentation and case discussion. Afterwards, the post-test was carried out with a total of 98 (73.68%) students. Data were collected by using a ‘Descriptive Characteristics Form’ and the ‘Perceptions of Nursing Diagnosis Survey’. In the statistical analysis of data, number, percentage, mean score and paired t-test were used. There was no statistical difference between the pretest and posttest total scores of the “Perceptions of Nursing Diagnosis Survey” before and after the online training for the nursing care plan process (p > 0.05). Students had a perception of nursing diagnoses at a moderate level. It was concluded that the case-based interventions had limited effects. The learning and use of the nursing diagnosis process by both nursing students and nurses facilitates its applicability in the field and makes it easier for nurses to provide more evidence-based care in the clinic. It is recommended that the teaching techniques used in the study be enriched and developed. Keywords: education, nursing diagnosis, nursing process, nursing students, perception Abstrak Pengaruh Pendidikan Proses Keperawatan terhadap Persepsi Mahasiswa tentang Diagnosis Keperawatan. Tujuan dari penelitian ini adalah untuk mengevaluasi pengaruh pendidikan proses keperawatan terhadap persepsi mahasiswa keperawatan tentang diagnosis keperawatan. Penelitian kuasi-eksperimental ini dilakukan pada mahasiswa tahun kedua yang mengambil mata kuliah keperawatan penyakit dalam. Seratus sebelas mahasiswa tahun kedua (91,72%) yang mengikuti pendidikan di fakultas keperawatan diikutsertakan dalam pre-test. Setiap sesi pelatihan yang diberikan kepada mahasiswa berlangsung selama 60 menit, dan total 12 sesi pelatihan diterapkan sebanyak tiga sesi per minggu. Pelatihan online diberikan kepada mahasiswa oleh seorang pendidik dengan presentasi dan diskusi kasus. Setelah itu, post-test dilakukan dengan total 98 (73,68%) mahasiswa. Data dikumpulkan dengan menggunakan 'Formulir Karakteristik Deskriptif' dan 'Survei Persepsi Diagnosis Keperawatan'. Dalam analisis statistik data, jumlah, persentase, skor rata-rata dan uji-t berpasangan digunakan. Tidak ada perbedaan statistik antara skor total pre-test dan post-test dari “Survei Persepsi Diagnosis Keperawatan” sebelum dan sesudah pelatihan online untuk proses rencana asuhan keperawatan (p > 0,05). Mahasiswa memiliki persepsi tentang diagnosis keperawatan pada tingkat sedang. Disimpulkan bahwa intervensi berbasis kasus memiliki efek yang terbatas. Pembelajaran dan penggunaan proses diagnosis keperawatan oleh mahasiswa keperawatan dan perawat memfasilitasi penerapannya di lapangan dan memudahkan perawat untuk memberikan perawatan yang lebih berbasis bukti di klinik. Disarankan agar teknik pengajaran yang digunakan dalam penelitian ini diperkaya dan dikembangkan. Kata Kunci: diagnosis keperawatan, mahasiswa keperawatan, pendidikan, persepsi, proses keperawatan